THE EDUCATIONAL POTENTIALS OF BAKA L.’S PACKETBOOKS : Received: 9th September 2025, Revised: 14th October 2025, Accepted: 17th October 2025, Date of Publication: 30th October 2025 - Dávid Szabó L,; Ilona Ponyiné Hatvani, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This study explores the Packetbook Project, an innovative initiative aimed at renewing Hungarian literature education in Slovakia. The primary objective of the project is to make students’ reading experiences more personal, relevant, and engaging by building on the freedom of choice, contemporary literature, and experiential pedagogical approaches. The paper provides an overview of the theoretical and methodological foundations of the Packetbook, investigates its pedagogical potential, and places special emphasis on the shift in assessment paradigms that align with its educational philosophy. At the core of this shift is the concept of formative assessment, which seeks not merely to evaluate students' performance but to actively support their learning progress. The Packetbook and formative assessment together constitute an interconnected framework that redefines the learning process as complex, personalized, and experience oriented.